CLASSROOM LANGUAGE EMPLOYED BY TEACHERS IN TEACHING EYL IN LUBUKLINGGAU - Ayu Oktaviani; Dwi Misgiyati (Universitas Jambi, 2019)
The objective of the research was to find out the classroom language used by the Primary teachers in EFL classroom. The sample of the research was 3 teachers in grade 2, 5 and 6 at Palm Kids Elementary School of Lubuklinggau. The samples were taken through non probability as the technique of sampling. The researcher used descriptive qualitative research and the data were collected by using observation, interview, and documentation(field note and video recording). The result revealed that Classroom Languages used by the English teachers’ were: Exclusive use of L1, Exclusive use of TL, and Use of L1 immediately followed by the equivalents in the other language. In the other English teachers’ responded towards are the classroom language used helping the students understood the meaning, made the students easier to understood the material, helped students to understand what English said, helped to explain the material more detail in teaching and learning process and made the students have to master English well.